2019
DOI: 10.9734/jalsi/2018/v19i430069
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm and Biosurfactant Mediated Aromatic Hydrocarbons Degradation by Marine Bacteria Isolated from Contaminated Marine Environments of Niger Delta

Abstract: Aims: To examine the effects of biofilm and biosurfactant associated cells of marine bacteria isolated from contaminated marine environments of Niger Delta on aromatic hydrocarbon degradation. Study Design: Nine treatments and the controls designs were set up in triplicates containing 100 mL of sterile modified mineral basal medium in 250 mL conical flasks supplemented with 50, 100, 200 and 300 ppm of xylene, anthracene and pyrene each and nine marine hydrocarbon degraders; incubated at 24°C for 5 - 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
(29 reference statements)
1
3
1
Order By: Relevance
“…Bergey's Manual of Determinative Bacteriology was used for the identification of the isolated bacterial strain S62A and on the basis of this manual, the strain S62A was tentatively identified as a member of genus Aeromonas hydrophilia. Several Gram-negative rod -shaped bacterial genera have been implicated, identified and documented as excellent biosurfactant producers (Nalini, and Parthasarathi, 2018;Uba et al, 2018;Araújo et al, 2019;Gomaa and El -Meihy, 2019;Ntshingila et al, 2022) and similar observation was made in this study. The application and suitability of biosurfactants in various industrial areas are depended on their stability against variable or extreme environmental settings of temperature, pH and salinity (Araújo et al, 2019).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Bergey's Manual of Determinative Bacteriology was used for the identification of the isolated bacterial strain S62A and on the basis of this manual, the strain S62A was tentatively identified as a member of genus Aeromonas hydrophilia. Several Gram-negative rod -shaped bacterial genera have been implicated, identified and documented as excellent biosurfactant producers (Nalini, and Parthasarathi, 2018;Uba et al, 2018;Araújo et al, 2019;Gomaa and El -Meihy, 2019;Ntshingila et al, 2022) and similar observation was made in this study. The application and suitability of biosurfactants in various industrial areas are depended on their stability against variable or extreme environmental settings of temperature, pH and salinity (Araújo et al, 2019).…”
Section: Resultssupporting
confidence: 88%
“…The low CMC value of the biosurfactant observed in this study could be due to its excellent formation and aggregation ability (Guo et al, 2022). This result is lower than the published report of Uba et al (2018) which stated that Bacillus cereus PYR9 had the highest reduction of 22.10 ± 8.9 mN /m in surface tension followed by Serratia marcescens XYL7 with 23.00 ± 8.50 mN /m and Alcaligenes faecalis PYR5 had the least reduction of 26.60 ± 8.90 mN /m. In another study by Ravindran et al (2020), they reported that the CMC from Bacillus subtilis was found to be 10 mg/mL which reduced the surface tension from 69.0 to 30 mN/m and that the decrease in surface tension could be as a result of sensitize biosurfactant from the optimized parameters.…”
Section: Resultscontrasting
confidence: 82%
See 3 more Smart Citations